A Case of Appendiceal Metastasis from Lung Cancer with Acute Appendicitis - Ohkouchi, Nobuhiro; Fukuzawa, Junya; Yamamoto, Masayoshi; Yanagisawa, Kazuhiko (Nippon Shokaki Geka Gakkai zasshi, 2007)
We repossrt a case of appendiceal metastasis from lung cancer with acute appendicitis. A 65-year-old man underwent left pneumonectomy and mediastinum lymphnode dissection for left lobe lung cancer at the age of 64. Nine months later, suffered recurrent lymph node metastasis undergoing radiation therapy. He suffered right lower abdominal pain during radiation therapy, found to be due to acute appendicitis with a tumor. He received antibiotic therapy with fasting, temporarily improving, but an appendicitis requiring surgery. The surgical specimen showed a 6cm mass on the back of the cecum. This tumor was diagnosed as appendiceal metastasis because the histology of carcinoma resembled the previous specimen from left lung cancer. Pathological findings showed poorly differentiated adenocarcinoma with abscess formation. Carcinoma mainly involves proper muscles and invades the mucosa and subserosa. He died of pneumonia 12 months after his last surgery. We discuss therapy for metastatic appendiceal tumor with appendicitis in cancer patients and review the literature.